Validity and reliability of the Cycleops Hammer cycle ergometer - Lillo-Bevia, J. R.; Pallarés, J. G. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To validate the new drive indoor trainer Hammer designed by Cycleops®. Methods: A total of 11 cyclists performed 44 randomized and counterbalanced graded exercise tests (100-500 W) at 70-, 85-, and 100-rpm cadences in seated and standing positions on 3 different Hammer units, while a scientific SRM system continuously recorded cadence and power output data. Results: No significant differences were detected between the 3 Hammer devices and the SRM for any workload, cadence, or pedaling condition (P value between 1.00 and .350), except for some minor differences (P=.03 and .04) found in the Hammer 1 at low workloads and for Hammer 2 and 3 at high workloads, all in seated position. Strong intraclass correlation coefficients were found between the power output values recorded by the Hammers and the SRM (=.996; P=.001), independently from the cadence condition and seated position. Bland-Altman analysis revealed low bias (-5.5 to 3.8) and low SD of bias (2.5-5.3) for all testing conditions, except marginal values found for the Hammer 1 at high cadences and seated position (9.6 [6.6]). High absolute reliability values were detected for the 3 Hammers (150-500 W; coefficient of variation <1.2%; SEM<2.1). Conclusions: This new Cycleops trainer is a valid and reliable device to drive and measure power output in cyclists, providing an alternative to larger and more expensive laboratory ergometers and allowing cyclists to use their own bicycles.